Hydrogen Peroxide Fuel Cells and Self-Powered Electrochemical Sensors Based on the Principle of a Fuel Cell with Biomimetic and Nanozyme Catalysts - Yunong Zhang; Yuxin Liu; Andreas Offenhäusser; Yulia Mourzina (Biosensors)
The operating principle of a fuel cell is attracting increasing attention in the development of self-powered electrochemical sensors (SPESs). In this type of sensor, the chemical energy of the analyzed substance is converted into electrical energy in a galvanic cell through spontaneous electrochemical reactions, directly generating an analytical signal. Unlike conventional (amperometric, voltammetric, and impedimetric) sensors, no external energy in the form of an applied potential is required for the redox detection reactions to occur. SPESs therefore have several important advantages over conventional electrochemical sensors. They do not require a power supply and modulation system, which saves energy and costs. The devices also offer greater simplicity and are therefore more compatible for applications in wearable sensor devices as well as in vivo and in situ use. Due to the dual redox properties of hydrogen peroxide, it is possible to develop membraneless fuel cells and fuel-cell-based hydrogen peroxide SPESs, in which hydrogen peroxide in the analyzed sample is used as the only source of energy, as both an oxidant and a reductant (fuel). This also suppresses the dependence of the devices on the availability of oxygen. Electrode catalyst materials for different hydrogen peroxide reaction pathways at the cathode and the anode in a one-compartment cell are a key technology for the implementation and characteristics of hydrogen peroxide SPESs. This article provides an overview of the operating principle and designs of H2O2–H2O2 fuel cells and H2O2 fuel-cell-based SPESs, focusing on biomimetic and nanozyme catalysts, and highlights recent innovations and prospects of hydrogen-peroxide-based SPESs for (bio)electrochemical analysis.